2017
DOI: 10.1108/srj-10-2015-0147
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability reports in Brazil through the lens of signaling, legitimacy and stakeholder theories

Abstract: Purpose The purpose of this paper is to extend the applicability of stakeholder, legitimacy and signaling theories by examining to what extent proactive corporate social responsibility disclosures are interrelated to attempt to gain and maintain legitimacy, to gain support of the stakeholders and to reduce information asymmetry. Design/methodology/approach To test the theoretical arguments, a longitudinal approach over a five-year period of 145 companies’ sustainability reports and statistical analysis was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 48 publications
0
67
0
5
Order By: Relevance
“…The organization's strategic decisions send signals to the market about commitment and initiatives that affect reputation and relationship with other organizations and stakeholders [34,35,40]. Moreover, positive signals increase firm value and performance, whereas negative signals reduce stock price and product demand [41,42].…”
Section: The Signaling Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The organization's strategic decisions send signals to the market about commitment and initiatives that affect reputation and relationship with other organizations and stakeholders [34,35,40]. Moreover, positive signals increase firm value and performance, whereas negative signals reduce stock price and product demand [41,42].…”
Section: The Signaling Theorymentioning
confidence: 99%
“…They find that in the SA region only Bangladesh and India have very limited research on CSR motivation. Furthermore, managerial research has been used in a very limited way in signaling theory [34][35][36] even though it has ample explanatory power in the economic perspective of sustainability disclosure and corporate governance elements. Therefore, our study shows the importance of performing a cross-country analysis of SA countries' corporate governance and total sustainability disclosure (economic, environmental, and social).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signaling theory shows that corporates, in this regard as "good" citizens, convey separate CSR information and are reported independently which shows a signal of their superior commitment to CSR activities (Mahoney et al, 2013). The corporate expects that their actions aside from reducing the asymmetry of information, also to benefit from their signaling actions through CSR (Ching and Gerab, 2017). External stakeholders who are interested in the information released by the corporate will look for additional information.…”
Section: Literature Review and Development Of Hypotesesmentioning
confidence: 99%
“…Stakeholder Theory showed that a company is not an entity that only operates for its own benefit but the company must provide benefits to stakeholders (shareholders, creditors, consumers, suppliers, governments, communities, analysts and others) [10,19]. One of the communities interest to the company is the company's concern for the environment.…”
mentioning
confidence: 99%